2015
DOI: 10.1186/s12245-015-0053-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic diagnostic procedures in severely injured patients - is only whole-body multislice computed tomography the answer?

Abstract: BackgroundWhole-body multislice computed tomography (WB-MSCT) has become an important diagnostic tool in the early treatment phase of severely injured patients. The optimal moment of WB-MSCT’s use during this treatment phase remains unclear. Many trauma centers use WB-MSCT in addition to conventional radiographs, while some trauma centers use WB-MSCT as the only radiological tool. The aim of this study was to determine the differences between these two protocols and to answer the question of whether convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
2
7
1
Order By: Relevance
“…Our study also demonstrated that CT panscans did not improve TTS or decrease LOS in the fragility fracture patient population, which directly contradicts the patterns seen in younger patient populations. 14,17 Our results support previous studies that have shown CT pan-scans in the elderly population have demonstrated a significant risk of incidental findings. The rate of unrelated findings in CT whole-body imaging has been reported as high as 50% and is known to be directly related to increasing age.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study also demonstrated that CT panscans did not improve TTS or decrease LOS in the fragility fracture patient population, which directly contradicts the patterns seen in younger patient populations. 14,17 Our results support previous studies that have shown CT pan-scans in the elderly population have demonstrated a significant risk of incidental findings. The rate of unrelated findings in CT whole-body imaging has been reported as high as 50% and is known to be directly related to increasing age.…”
Section: Discussionsupporting
confidence: 90%
“…12,16 Several studies have shown some benefit, such as preventing under triage, decreased time to diagnosis, and improved diagnostic accuracy. 3,17,20,21 However, these studies address the general trauma population or any trauma occurring in the geriatric population. To our knowledge, no study has directly addressed orthopedic management in patients who have sustained fragility fractures and are subject to this diagnostic strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a trauma room algorithm has become widely accepted in Germany which is based on Advanced Trauma Life Support (ATLS ® ) and the European Trauma Course [ 3 – 5 ]. Nevertheless, the imaging technique to be used in the trauma room setting continues to be a matter of debate on account of time constraints, the level of radiation exposure, the patient’s overall condition, and other factors [ 6 – 8 ]. Computed tomography (CT), and in particular modern multi-slice computed tomography (MSCT), has become the standard imaging modality for diagnosing thoracic injuries [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the latter, the pre-test likelihood of an unsuspected injury is high implying that widespread use of immediate SWBCT may be justified. Interestingly, two different analyses of patients included in the TraumaRegister DGU® of the German trauma society concluded conflictingly with regard to the potential survival benefit of immediate SWBCT [16,18,69].…”
Section: Discussionmentioning
confidence: 99%